Cultural effects on computational metrics of spatial and temporal context - Nicholas D. Wright (Nature Portfolio, 2018)
Abstract The concept of “prediction error” - the difference between what occurred and was expected - is key to understanding the cognitive processes of human decision making. Expectations have to be learned so the concept of prediction error critically depends on context, specifically the temporal context of probabilistically related events and their changes across time (i.e. volatility). While past research suggests context differently affects some cognitive processes in East Asian and Western individuals, it is currently unknown whether this extends to computationally-grounded measures of learning and prediction error. Here we compared Chinese and British nationals in an associative learning task that quantifies behavioural effects of prediction error, and—through a hierarchical Bayesian learning model—also captures how individuals learn about probabilistic relationships and their volatility. For comparison, we also administered a psychophysical task, the tilt illusion, to assess cultural differences in susceptibility to spatial context. We found no cultural differences in the effect of spatial context on perception. In the domain of temporal context there was no effect of culture on sensitivity to prediction error, or learning about volatility, but some suggestion that Chinese individuals may learn more readily about probabilistic relationships.